Efficacy and safety of direct‐acting antiviral‐based treatment in hepatitis C virus infected patients with chronic renal function impairment: An updated systemic review and meta‐analysis. Issue 11 (12th March 2020) - Yang, Hongling; Hu, Xiao; Pu, Lei; Ren, Song; Feng, Yunlin
Abstract: Objective: To further determine the efficacy and safety of direct‐acting antiviral (DAA)‐based treatments in hepatitis C virus (HCV) infected patients with renal function impairment. Methods: MEDLINE, EMBASE and the Cochrane Library were searched for relevant studies. All studies assessing the efficacy and safety of DAA‐based treatments against HCV infection in patients with renal impairment and HCV infection were eligible for inclusion. Outcomes assessed included efficacy outcomes and safety outcomes. Summary estimates were obtained using an inverse‐variance weighted random effect model and Freeman‐Tukey double arcsine transformation. Results: Twenty‐seven studies (n = 1048 participants) were included. The majority of included studies were of fair quality with Newcastle‐Ottawa scale scores between 4 and 6. The pooled virologic response rates at the end of treatment or 4, 12, 24 weeks after treatment (ie, EOTR, SVR4, SVR12 and SVR24 rates) were 97.0% (95% confidence interval [CI], 94.0%‐99.0%), 80.9% (95% CI, 49.3%‐98.7%), 94.1% (95% CI, 91.6%‐96.3%) and 89.6% (95% CI, 75.5%‐98.1%), respectively. The pooled relapse rate was 6.4% (95% CI, 3.4%‐10.4%). The pooled incidence of adverse events and severe adverse events leading to discontinuation were 47.6% (95% CI, 35.0%‐60.4%) and 2.9% (95% CI, 1.4%‐5.0%), respectively. High heterogeneity among studies exists for SVR4 and SVR24 rates. Formal statistical testing did not identify the presence of publication bias for all measured outcomes except the relapse rate. Conclusion: The results support the efficacy and safety of DAA‐based treatments in this population. Future studies with better design, larger sample size and longer follow up will be the next step. SUMMARY AT A GLANCE This systematic review evaluated the efficacy and safety of direct‐acting antiviral based therapies in hepatitis C infection in patients with renal impairment. The majority of studies were of fair quality only. These therapies were found to be highly efficacious although there were high rates of adverse events.